The Impact of Dietary Folate Intake on Reproductive Function in Premenopausal Women: A Prospective Cohort Study - Gaskins, Audrey J.; Mumford, Sunni L.; Chavarro, Jorge E.; Zhang, Cuilin; Pollack, Anna Z.; Wactawski-Wende, Jean; Perkins, Neil J.; Schisterman, Enrique F. (PLOS ONE, 2012)
Background Folic acid is recommended to reproductive-aged women to prevent birth defects, though little is known about the effects of dietary intake on other reproductive outcomes. Improved pregnancy rates have been documented after folic acid supplement use, suggesting a possible link with ovulation, however research is limited. Our objective was to evaluate the association between dietary folate intake, hormone levels, and sporadic anovulation in healthy, regularly menstruating women. Methodology/Principal Findings The BioCycle study (2005–2007) prospectively followed 259 healthy women aged 18–44 years from the western New York region for up to 2 menstrual cycles. Total folate and specific sources of folate were assessed up to 4 times per cycle by 24-hour recall. Estradiol, progesterone, luteinizing hormone, and follicle-stimulating hormone were measured in serum up to 8 times per cycle, timed using fertility monitors. Anovulation was defined as a cycle with peak progesterone concentration ≤5 ng/mL and no LH peak in the mid/late luteal phase. Higher intake of dietary folate (in dietary equivalents) across tertiles had a marginally significant association with greater luteal progesterone levels (P trend 0.08). Higher intake of synthetic folate was significantly associated with higher luteal progesterone levels (P trend 0.05). Specifically, women in the 3rd tertile of synthetic folate intake had, on average, 16.0% (95% CI, 0.5–33.8%) higher luteal progesterone levels compared to women in the 1st tertile. Moreover, consumption of synthetic folate was significantly and inversely associated with anovulation such that women in the 3rd tertile had a 64% (95% CI, 8–86%) decreased odds of anovulation compared to the women in the 1st tertile (P trend 0.03). Conclusions/Significance These findings suggest that a diet high in synthetic folate may be associated with increased progesterone levels and lower risk of sporadic anovulation. Further study of the effect of dietary folate and folic acid supplement use on reproductive health is warranted.